2016
DOI: 10.3897/neobiota.31.9185
|View full text |Cite
|
Sign up to set email alerts
|

Biological invasions and natural colonisations are different – the need for invasion science

Abstract: In a recent Discussion Paper, Hoffmann and Courchamp (2016) posed the question: are biological invasions and natural colonisations that different? This apparently simple question resonates at the core of the biological study of human-induced global change, and we strongly believe that the answer is yes: biological invasions and natural colonisations differ in processes and mechanisms in ways that are crucial for science, management, and policy. Invasion biology has, over time, developed into the broader transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 49 publications
1
40
1
1
Order By: Relevance
“…We agree with Wilson et al (2016) on the differences of mechanisms (including the degree [rate] at which they occur), as well as their implications, especially for management and policy. But absolutely nowhere have Wilson et al (2016) demonstrated that the two are subject to a different process.…”
Section: Humans Have a Huge Influence On Many Phenomenasupporting
confidence: 73%
See 3 more Smart Citations
“…We agree with Wilson et al (2016) on the differences of mechanisms (including the degree [rate] at which they occur), as well as their implications, especially for management and policy. But absolutely nowhere have Wilson et al (2016) demonstrated that the two are subject to a different process.…”
Section: Humans Have a Huge Influence On Many Phenomenasupporting
confidence: 73%
“…We agree with Wilson et al (2016) that scientific testing of hypotheses should determine whether colonisation and biological invasions are truly unique, or just the same overall process initiated by different mechanisms. Naturally there would be huge differences if the focus was at the level of mechanisms such as pathways (i.e.…”
Section: Humans Have a Huge Influence On Many Phenomenamentioning
confidence: 54%
See 2 more Smart Citations
“…The pathways for IASs arriving at islands are a subset of those for IASs in general, where long-distance transportation by marine vessel and aircraft naturally dominates (Hulme 2009). This makes the dispersal of IASs to islands different in rate and type from both continents and natural colonizations (Wilson et al 2016). Due to delays in reporting, new IASs on islands can take over a decade to enter records (Seebens et al 2017), and an invasion debt is created by biological lag effects for IASs that have already arrived but are not yet established or expanded on islands (Essl et al 2011).…”
Section: Indicatorsmentioning
confidence: 99%